Effect of Native Spleen Preservation in an Experimental Model of Modified Multivisceral Transplantation. (July 2018) - Stringa, Pablo; Vela, Maria; Arreola, Monserrat; Navarro, Pablo Gonzalez; Moreno, Ane M Andres; Boluda, Esther Ramos; Granados, Eduardo Lopez; Rumbo, Martin; Del Carmen Mendez Diaz, Maria; Collazo, Eduardo Lopez; Martinez, Antonio Perez; Oliveros, Francisco Hernandez
Abstract : Introduction: Native spleen is usually removed in patients undergoing modified multivisceral transplantation (MMVT) increasing the risk of sepsis and graft-versus-host disease (GVHD). On the other hand, it has been reported that spleen preservation also increases the risk of allograft rejection. The mechanisms of theses effects including mixed chimerism level are poorly understood. Based on a novel experimental model of MMVT that triggers GVHD, we hypothesized that native spleen preservation attenuate GVHD after MMVT. Methods: Isolated heterotopic intestinal transplantation (IT) or heterotopic MMVT from Lewis (LEW) to Brown Norway (BN) rats was performed. IT graft consisted in 80% of the small bowel, and MMVT graft consisted of the distal half of the stomach, duodenum, pancreas, spleen and the small bowel of the donor. The native spleen was removed (MVM-S) in half of the MMVT recipients (N=5), while the remaining preserved their own spleen (MVM+SP) (N=5). After MMVT or IT, the mixed hematopoietic chimerism was determined in peripheral blood samples by flow cytometry using strain-specific HLA antibodies and clinical signs of GVHD such as skin rash were evaluated. Results: All animals in the group MVM-S presented clinical signs compatible with GVHD such as skin rash, weight loss, and diarrhea, among others, between 7 and 10 days after transplantation. Skin rash was particularly remarkable in the ears, snout and periocular area. Clinical signs of GVHD were less frequent in MVM-S and IT animals (100% vs 40% and 40%, p<0.05) Flow cytometry found that mixed chimerism was significantly higher in the MVM-S group, compared to the MVM+SP group (percentage donor's lymphocytes in peripheral blood at 3 and 7 post-transplant days (PTD): 36, 6% (30-53%) and 9, 4% (3-18%) vs 23, 6% (19-26%) and 20, 5 (18-25, 5%) respectively; p<0.05) (Figure 1). The level of chimerism gradually decreased as clinical signs of rejection appeared. Figure. No caption available. Conclusion: Allogeneic heterotopic MMVT in the strain combination L-BN yielded a higher rate of GVHD compared to IT. Native spleen preservation in MMVT recipients attenuated the occurrence of GVHD and reduced the level of chimerism compared to recipients that underwent spleen removal during the transplant. Further experimental studies are warranted to clarify the mechanisms of the spleen immune effects over GVHD, chimerism and rejection; however, the results shown in this work strongly support the importance of this organ in the field of intestinal transplantation.